2019
DOI: 10.1186/s12889-019-7954-z
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in ferry shipping employees: the role of work-family conflict and supervisor support

Abstract: BackgroundFatigue is a concern in ferry shipping as it has a negative impact on crew members health and plays a major role in marine incidents and accidents. Research within land-based occupational settings has found that work-family conflict is an important risk factor for fatigue and that support from leaders constitutes a possible resource with the potential to buffer a negative impact from work-family conflict. Though, the working conditions of ferry shipping are likely to interfere with employee’s family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 63 publications
1
19
1
1
Order By: Relevance
“…This study found differently of the factor of work-family con ict with the Dohrmann et al's study [14].…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…This study found differently of the factor of work-family con ict with the Dohrmann et al's study [14].…”
Section: Discussioncontrasting
confidence: 60%
“…Dohrmann et al [14] study found that the fatigue among the ferry shipping crews was associated with work-family con ict and supervisor support. In their study, these two factors were signi cantly associated with the two sub-dimensions of fatigue, including physical exertion and physical discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true in real-world situations, where some jobs require sustained concentration, such as police officer, medical worker, and pilot. These occupations often endure long work hours with high stress, increasing the risk of accidents that lead to injury and substantial economic loss ( Ricci et al, 2007 ; Fekedulegn et al, 2018 ; Jensen, 2018 ; Dohrmann et al, 2019 ; De Jong et al, 2020 ). Moreover, people in a state of constant fatigue over a long period have a higher risk of morbidity ( De Vries et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research focused on a theoretical path-driven analysis that distinguishes the causes of job financial support, work tension, burnout, and desire to quit a job between age categories. The findings of many studies suggest that the mechanisms of work pressure, fatigue, and desire to leave (Dohrmann et al, 2019;Oldenburg et al, 2013;Techera, 2017). Working together or social capital factors have been more prominent in defending elderly employees from workplace pressures relative to unskilled employees (Boyas et al, 2012).…”
Section: Introductionmentioning
confidence: 99%